2021
DOI: 10.1021/acs.organomet.1c00201
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselectivity in the Noyori–Ikariya Asymmetric Transfer Hydrogenation of Ketones

Abstract: Asymmetric transfer hydrogenation (ATH) is an important catalytic process in the fragrance and pharmaceutical industries. The Noyori–Ikariya chiral molecular ruthenium complex has been the catalyst of choice for this reaction for over 25 years. The mechanism and origin of enantioselectivity have irked chemists ever since the catalyst conception. This work addresses important shortcomings in understanding the origin of enantioselectivity with the Noyori–Ikariya catalysts, traditionally associated with the CH−π … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…Numerous experimental and computational studies of ( R , R )- 3 and its derivatives have indicated that the stereochemistry of the product is driven by a C–H···π interaction between mesitylene and the acetophenone phenyl ring, which helps to stabilize the transition state for the formation of R -1-phenylethanol (Scheme a). ,,,, Reverse binding to give the S -1-phenylethanol product was found to be disfavored by a repulsive interaction between the lone pair on the sulfone and the substrate arene ring, further reinforcing the product enantioselectivity (Scheme b).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous experimental and computational studies of ( R , R )- 3 and its derivatives have indicated that the stereochemistry of the product is driven by a C–H···π interaction between mesitylene and the acetophenone phenyl ring, which helps to stabilize the transition state for the formation of R -1-phenylethanol (Scheme a). ,,,, Reverse binding to give the S -1-phenylethanol product was found to be disfavored by a repulsive interaction between the lone pair on the sulfone and the substrate arene ring, further reinforcing the product enantioselectivity (Scheme b).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, further investigation into such a catalytic system would not only help shed light on the intricate origin of enantioselectivity in this important catalytic reaction, but also stimulate understanding on the underlying principles of π interactions as well as developing catalysts with assembling properties based on these non-covalent forces. To the best of our knowledge, very few examples exist that use such weak yet essential non-covalent π interactions as the control elements in asymmetric catalytic reactions 45 , 46 .…”
Section: Introductionmentioning
confidence: 99%
“…After more than two decades since the Nobel‐Prize‐winning developments in asymmetric TH (ATH) by Noyori, [4] molecular catalysts centered on Ru have remained of great interest to the chemical community. The origin of enantioselectivity is a result of a dynamic interplay of non‐covalent interactions within the transition state that ultimately determines enantiomeric excess [5] . Ligand design has played an important role in Ru‐catalyzed ATH and has led to the gram‐scale synthesis of chiral exocyclic allylic alcohols and cis ‐β‐substituted α‐hydroxybutyrolactone, which have otherwise been difficult to isolate [6]…”
Section: Introductionmentioning
confidence: 99%